Pretzel et Bretzel: lecture et analyse événementielles des signaux de parole pour l’étude des consonnes occlusives de l’alsacien - Steiblé, Lucie; Sock, Rudolph (Neophilologica, 2014)
Articulatory-acoustics events and the relations that tie them together are crucial to understanding proper speech functioning. The features at the phonological level and the cues studied in phonetics are related to specific speech events, visible for example in acoustic signals. Thus, a close analysis of these events allows us to understand which relations underpin the system of contrasts. This article deals with Alsatian stops, taking into account the feature [voice]. A number of questions relating to the nature of the plosives are not solved. These questions are representative of difficulties in analyzing a system of fragile oppositions which nevertheless is operational and fluent. So, we shall thus present a classification of the consonants of Alsatian. We shall begin by evoking problems posed by the classification of plosives, through features and cues. We shall use the results obtained during experimental analyses of the speakers of Colmar, the results of which might demonstrate the importance of understanding the event structure of these consonants, in order to classify them at a convincing phonological level.